EXPLORING THE IMPACT OF TELEMEDICINE ON ACCESS TO HEALTHCARE IN RURAL COMMUNITIES - Asmirati Yakob; Nina Anis; Rashid Rahman (Yayasan Adra Karima Hubbi, 2026)
The rapid advancement of telemedicine has revolutionized healthcare delivery, particularly in rural areas where access to healthcare services is often limited. This study explores the impact of telemedicine on improving healthcare access in rural communities, aiming to evaluate how virtual healthcare platforms can overcome geographical barriers and enhance patient outcomes. The research employs a mixed-methods approach, combining qualitative interviews with healthcare professionals and patients in rural settings, along with quantitative surveys to assess healthcare accessibility, satisfaction, and perceived effectiveness. The findings reveal that telemedicine significantly improves access to healthcare by reducing travel time, minimizing wait times for appointments, and offering continuous care, which is crucial for managing chronic conditions. Furthermore, patients expressed high satisfaction with the convenience and affordability of virtual consultations. However, challenges such as limited internet connectivity, technological literacy, and concerns about the quality of care were noted. In conclusion, telemedicine holds great potential in expanding healthcare access in rural communities, but it requires tailored strategies to address infrastructure gaps and ensure equitable access to all individuals. Future research should focus on the long-term outcomes and scalability of telemedicine initiatives in diverse rural settings.